Investigation of Jet-to-Jet Interaction in Sprays for DISI Engines - Heldmann, Markus; Bornschlegel, Sebastian; Wensing, Michael (SAE Technical Papers, 2015)
Jet-to-jet interaction has a strong influence on the targeting and spray behavior of injection nozzles for DISI engines. In the superheated flashboiling regime especially, the spray shape and properties can change drastically due to interaction between spray jets. In this work, two setups are shown to investigate this effect, using shadowgraphy, phase doppler anemometry (PDA) and laser-induced fluorescence (LIF). The influence of spray properties and ambient conditions can be shown by comparing a commonly used multi-hole injector with a colliding jet atomization concept with well-known and significantly differing spray properties.
Created from Fastlane, Scopus look-up